The Commodification of the American West: Marketers’ Production of Cultural Meanings at the Trade Show - Peñaloza, Lisa (Journal of Marketing, 2000)
The author employs critical ethnographic methods to examine empirically marketers’ processes of producing cultural meanings at a western stock show and rodeo. Western cultural meanings and values of freedom, naturalism, competition, and family values are produced by marketers in attracting a nonranch audience; juxtaposing business, education, and entertainment; making ample references to historical tradition; and using business activity as the basis for claims of authenticity. Marketing implications center on tapping into rich sources of cultural meaning by (1) attending to the cultural dimensions of economic activity, (2) taking industry as the unit of analysis through an examination of representations of production in market discourses and practices, (3) expanding history from a research method to a source of market meaning, and (4) considering the marketplace as a lived tradition.